U is for undertow - Ordóñez Diví, Victoria (New York : Berkley Books, 2010)
When she is hired by a preppy college dropout to discover what happened to a four-year-old girl who disappeared more than twenty years earlier, Kinsey Millhone investigates the young man's sketchy memories about a burial scene he believes he discovered at the age of six.